The house of Kwee Sik Poo; An Indonesian-Chinese merchant from Pasuruan - Sien, Kwee Hong (UI Scholars Hub, 2017)
The Kwee family is an old Indonesian-Chinese family from Pasuruan, in East Java, and one of a few merchant families of either Chinese or Arab ethnic origin which led successful lives in this small town in the nineteenth century. From their Chinese ancestral village, Liu Chuan in Fujian province, China, a Kwee ancestor travelled to Southeast Asia and settled in Pasuruan, probably in the eighteen century. As with many families who held important positions in the ethnic Chinese community, it also owned large homes, mostly in a mixed architectural style, called